Two New Species of Emesis Fabricius, 1807 from Northwestern South and Central America (Lepidoptera: Riodinidae) - Callaghan, Curtis John; Trujano-Ortega, Marysol; Ríos-Málaver, Indiana C. (Zootaxa, 2024)
Two new species and a subspecies, Emesis (Aphacites) hypoaithos, Callaghan, Trujano-Ortega & Ríos-Málaver, sp. nov., Emesis (Aphacites) hypoaithos ochros, Callaghan, Trujano-Ortega & Ríos-Málaver, ssp. nov., Emesis (Tenedia) pacis, Callaghan, Trujano-Ortega & Ríos-Málaver, sp. nov. are described from Northwestern South and Central America. The biology, habits, habitat, and distribution of these taxa are described from museum specimens and field observations. Male and female genitalia of the new taxa are illustrated and compared with similar taxa for proper identification.